MOTIVES OF CYPTOCURRENCY TAX AVOIDANCE - Limantoro, Amedea Cristabel; Rahmiati, Alfa (Widya Mandala Surabaya Catholic University, 2023)
Research Purposes. This study aim to find out the motives of cryptocurrency investors to carry out tax non-compliance behavior, people who influence, and obstacles that may reduce the desire to carry out tax violations.Research Methods. The research was conducted with an exploratory approach.Research Results and Findings. The results of the research are the motives owned by cryptocurrency investors in carrying out tax non-compliance behavior are saving personal finances, dissatisfaction with the taxation system, distrust of tax handlers, burdensome tax rates, and newest policies which contrary to the principle of decentralization. People who influence cryptocurrency investors in committing tax non-compliance are friends, cryptocurrency communities, family, and colleagues. Things that can hinder cryptocurrency investors from carrying out tax non-compliance are the lack of loopholes, tax avoidance schemes which difficult to implement, the potential of inspected by the tax authorities, the potential of sanctions, and the potential of reported by third parties (the exchangers).